Scoping review of brucellosis in Armenia: persistent neglect, significant knowledge gaps, and a necessity for innovative research, surveillance, and control - Yeritsyan, Anna; Laine, Christopher G.; Danelyan, Hrant; Tumanyan, Pertsh; Arenas-Gamboa, Angela M. (Frontiers in Veterinary Science, 2025)
Brucellosis is a zoonotic disease of nearly worldwide distribution. Despite its endemic presence in many regions, the true burden of the disease remains poorly defined. Armenia, a small country situated in the South Caucasus, exemplifies this lack of clarity. To better understand the epidemiological landscape of brucellosis in Armenia, we conducted a scoping review of studies addressing both human and animal brucellosis within the country. Comprehensive database and manual searches identified only 19 relevant articles published between 1982 and 2023. Reported individual seroprevalence estimates for animal brucellosis ranged dramatically from 0.26 to 18.04% (median—3.33%) in cattle and from 0.75 to 29.90% (median—1.94%) in small ruminants. Only one study investigated swine; however, the sample size was too small and precluded meaningful interpretation. None of the studies identified the Brucella species or strains involved, leaving unresolved the question of the primary livestock reservoirs. In humans, brucellosis was predominantly reported among individuals residing in rural areas, with an average incidence of approximately 8 cases per 100,000 population per year. Although constrained by limitations due to the scarcity of available data, this review highlights the neglected nature of brucellosis in Armenia underscoring the potential public health risk posed by this bacterium. Reporting inconsistencies, the absence of readily available diagnostic tools, and the lack of standardized testing procedures hinder an accurate assessment of the disease burden. This review summarizes and identifies critical gaps in research and control efforts, offering insight that can support the need for a comprehensive, long-term national surveillance and control strategy.